Publication characteristics of oral presentations at the European Society of Cardiovascular Radiology congresses - Hamza Eren Güzel; Ali Salbas; Özgür Yaşar; Alperen Erboğa; Babak Saravi (Frontiers in Cardiovascular Medicine, 2026)
Background Scientific congresses are important platforms for the early dissemination of research findings; however, not all presented abstracts subsequently reach full-text publication. Although congress-to-publication outcomes have been examined for several radiology meetings, the European Society of Cardiovascular Radiology (ESCR) congress has not been specifically evaluated. This study aimed to evaluate the publication outcomes of ESCR oral presentations, explore univariable associations between presentation characteristics and subsequent publication, and characterize temporal changes in research patterns. Methods Oral presentations from the ESCR congresses held between 2019 and 2022 were retrospectively reviewed. The 2018 and 2023 joint meetings with the European Society of Thoracic Imaging were excluded to reduce heterogeneity. Abstracts published before the corresponding congress and duplicate presentations were excluded. Publication was defined as subsequent full-text original research indexed in PubMed; searches were conducted between April 24 and May 10, 2026. Country of origin, subspecialty, study design, and collaboration type were recorded. Associations with publication outcome were assessed using chi-square tests or an exact test for sparse country-level data. A standardized 36-month analysis was used for congress-year comparisons, and temporal changes in study design and collaboration were evaluated. Results Of 291 oral presentations, 145 were subsequently published as PubMed-indexed full-text original research articles, yielding a publication rate of 49.8%. Median time to publication was 13.0 months, and 89.7% of published studies appeared within three years. Publication outcome differed significantly by country of origin, subspecialty, and study design, whereas collaboration type was not significantly associated with publication. Publication rates did not differ across congress years ( p = 0.726), including with standardized 36-month follow-up ( p = 0.478), whereas study-design and collaboration distributions changed significantly over time (both p < 0.001). Conclusion Approximately half of ESCR oral presentations progressed to PubMed-indexed full-text original research, and most identified publications appeared within three years. Publication conversion remained stable across congress years, whereas the design and collaborative structure of presented research changed over time. As the first ESCR-specific congress-to-publication analysis, these findings provide a benchmark for research dissemination in cardiovascular radiology; however, restriction to PubMed may underestimate the overall full-text publication rate.